Aprendizagem de Química no ensino na Educação Básica : uma sequência didática utilizando textos de divulgação científica - Chaves, Maria Amélia Lucas (2018)
This research aims to verify the contribution of a Didactic Sequence (DS) using Scientific Dissemination Texts (SDT) to learn the curricular contents of chemistry in Basic Education. At the present time schools have the important mission of encouraging students to read various textual genres. In the discipline of chemistry the reading of SDT can contribute to the learning of the curricular contents predicted in the guiding documents of basic education. In this context the SDT has the mission to lead the community to know the various scientific advances that influence the quality of life of individuals. The study is characterized as a qualitative research, where, at the beginning, a sample of fifty texts from the World Session of the Scientific Dissemination magazine Ciência Hoje, which can be used in the teaching of chemistry, was selected for analysis. Among the texts analyzed, sixteen SDT were selected, more correlated to the curricular contents predictes in the official documents for the series of the students of the second year of high school. During the development of DS the students performed various activities, always on orientation. After the conclusion of the DS the students answered a questionnaire about questions pertinent to the work developed and participated in a focus group to collect information for the evaluation of the DS developed and thus reveal the contributions of the SDT to the learning of the curricular contents of chemistry. The results obtained through the procedures used to evaluate the DS, showed that the pedagogical proposal used for the learning of chemistry was positively accepted by the students who besides being interested in reading the texts, managed to make the necessary inferences and associations with the curricular contents studied . It is believed that the use of diversified learning methodologies was a factor that motivated students' motivation for learning from the reading of DS.